2007
DOI: 10.1111/j.1439-0418.2007.01165.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bemisia tabaci honeydew and its carbohydrates on search time and parasitization of Encarsia bimaculata

Abstract: The search time of Encarsia bimaculata Heraty et Polaszek was examined and recorded by using filter paper discs in Petri dish arenas impregnated with Bemisia tabaci (Gennadius) honeydew or its component carbohydrates. Our data show that E. bimaculata used honeydew as a contact kairomone to locate its host. Females responded quantitatively to the honeydew and the search time in the treated patches increased. This increase was concentrationdependent with regard to the amount of honeydew applied, but it levelled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
0
15
1
Order By: Relevance
“…nr. furuhashii than glucose or sucrose (Mandour et al, 2005(Mandour et al, , 2007, differing from the results obtained from En. formosa, En.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…nr. furuhashii than glucose or sucrose (Mandour et al, 2005(Mandour et al, , 2007, differing from the results obtained from En. formosa, En.…”
Section: Discussioncontrasting
confidence: 52%
“…In B. curculionis, there was no significant difference in longevity between trehalose-fed and sucrose-fed females, but glucose and fructose alone appeared to have the most benefits while trehalose was not as useful for increasing parasitoid longevity (Jacob and Evans, 2004). In addition, Mandour et al (2007) showed that trehalose had a significantly lower effect on female longevity of En. bimaculata than glucose and sucrose, but almost the same effect as fructose, and Mandour et al (2005) reported a similar result for Er.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The B. tabaci population used in this study was originally collected from hibiscus plants grown in the horticultural unit of South China Agricultural University (SCAU). Whiteflies ( B. tabaci ) and parasitoids ( E. bimaculata ) were reared following the methods of Qiu et al (2007a, b) and Mandour et al (2006, 2007a, b). Colonies were maintained on hibiscus plants housed in rearing cages (60 × 60 × 60 cm) in the laboratory for at least 10 generations before used in experiments.…”
Section: Methodsmentioning
confidence: 99%